Challenges and Opportunities for Policy Formulation of Special Economic Zones in Indonesia: A Review of the Contemporary Systematic Literature - A. Ariyadi Adi; M. Akbar Akbar; Andi Muhammad Ishak Ismail Ishak; Safaruddin Safar (Journal of Social and Policy Issues, 2026)
This study examines the challenges and opportunities in the formulation of Special Economic Zones policies in Indonesia to support inclusive and sustainable economic growth. This study uses a bibliometric approach with data sources obtained from the Dimensions database, where publications are selected based on the keyword "policy formulation" in the period 2015–2024. Data is analyzed and visualized using VOSviewer to identify research trends, thematic clusters, and relationships between key concepts. The results show that publications related to policy formulation have increased steadily until 2022, then decreased in the following years. In Special Economic Zones, the main challenges found include regulatory uncertainty, limited infrastructure, land acquisition, weak coordination between stakeholders, and the need for socio-environmental integration. Nevertheless, Special Economic Zones still have an important role in attracting investment, creating jobs, strengthening regional competitiveness, and encouraging local economic development. The limitation of this research lies in the use of a single database, so further research needs to integrate various data sources as well as empirical approaches. Practically, the results of this study provide input for policymakers in designing Special Economic Zone policies that are more adaptive, contextual, and inclusive through improved governance, regulatory certainty, infrastructure readiness, and community involvement.